DESAIN DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN DALAM PENENTUAN DOSEN PEMBIMBING TUGAS AKHIR DI POLTEKBA - Ihsan Ihsan; Dwi Lesmideyarti (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
In determining the final project supervisor in making a decision by the department at the Balikpapan State Polytechnic, there are several factors that become criteria. This assessment is based on 3 criteria which will be divided into several sub-criteria, namely the first, namely Education, the sub-criteria are the subjects taught and areas of expertise, the second is lecturer research, the sub-criteria are research topics and theses, and the third is supporting the sub-criteria are training or workshops that have been attended. For the sake of efficiency and effectiveness of the department, the right decision making is very necessary. This study is used to build a decision-making system that has the ability to analyze in determining the final project supervisor using the profile matching method, where each criterion in this case the assessment factors and alternative supervisors is compared with one another so as to provide an output value priority intensity that produces a system that provides an assessment of each supervisor. This decision-making system can assist the department in determining the final project supervisor based on the criteria and weighted values. The application of this system is very useful to facilitate decision making related to the determination of the final project supervisor, so that the most appropriate final project supervisor will be obtained to guide students according to the competence of the lecturer and the theme of the student's final project.